A review on recent advances in the application of biosurfactants in wastewater treatment. (December 2021) - Malkapuram, Surya Teja; Sharma, Vikrant; Gumfekar, Sarang P.; Sonawane, Shirish; Sonawane, Shriram; Boczkaj, Grzegorz; Seepana, Murali Mohan
Abstract: Microorganisms produce a variety of non-conventional surface-active molecules, known as biosurfactants. The biosurfactants find diverse applications in the oil industry, agriculture, emulsifiers, and wastewater treatment, to name a few. Since they are produced from microbes, advantages such as biodegradability, lower toxicity, and environmental compatibility can be leveraged compared to the chemical surfactants. Recently, biosurfactants found potential usability in treating wastewater generated from various domestic, industrial, and agricultural sources. The application of biosurfactants in wastewater treatment is mainly due to their excellent foaming ability, specific activity, and high selectivity under wide operation window of temperature, pH, and salinity. Wastewater treatment with use of low cost biosurfactant is one of the important suitable goal in treating the wastewater since biosurfactants can be produced from cheap material and cause less damage to the environment by replacing surfactants produced from petroleum crude. This review focuses on the recent developments in biosurfactant production using waste materials such as food and agricultural residues, industrial waste, and animal waste and their application in wastewater treatment processes such as contaminant degradation, oil–water separation, heavy metal removal, and effluent flotation. The characteristics of the biosurfactants produced from cheap materials are compared with that of synthetic surfactants. In fact, the characteristics of both types of surfactants are found to be similar. The ability of biosurfactants for pollution removal from wastewater is extensively reviewed and presented. Finally, the review also evaluates the economic feasibility of biosurfactant production on commercial scale and their industrial scale wastewater treatment application.